2009
DOI: 10.1128/cvi.00062-09
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Longevity of Antibody Response to Influenza A H5N1 Virus Infection in Humans

Abstract: Anti-H5N1 antibody was determined by microneutralization, hemagglutination inhibition, and Western blotting assays in serial blood samples collected from eight Thai patients, including four fatal cases and four survivors. The antibody was detected as early as 5 days and, typically, with an increase in titer in paired blood at about 15 days after disease onset. The anti-H5 antibody response was long-lasting, for almost 5 years in cases which can be followed that far. In addition, cross-neutralizing activity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 10 publications
3
40
0
1
Order By: Relevance
“…[21][22][23][24] Looking at the kinetics of immune responses from a different angle, antibody responses to influenza A H5N1 virus infection in fatal cases and survivors showed that high neutralizing antibody titers were achieved only 2 to 3 weeks after symptom onset in the majority of H5N1-infected individuals tested. 25 Further, only one out of five patients had a significant antibody response within 5 d after the onset of disease. Infection should be an even stronger antigen challenge than any vaccination, so these data demonstrate that clinically relevant antibody responses are unlikely to occur within the first 7 d.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Looking at the kinetics of immune responses from a different angle, antibody responses to influenza A H5N1 virus infection in fatal cases and survivors showed that high neutralizing antibody titers were achieved only 2 to 3 weeks after symptom onset in the majority of H5N1-infected individuals tested. 25 Further, only one out of five patients had a significant antibody response within 5 d after the onset of disease. Infection should be an even stronger antigen challenge than any vaccination, so these data demonstrate that clinically relevant antibody responses are unlikely to occur within the first 7 d.…”
Section: Discussionmentioning
confidence: 99%
“…Pada saat gejala dini pada umumnya dokter lebih sering menduga penyakit lain yang lebih sering terjadi seperti infeksi dengue. 25 Rapid diagnostic test untuk influenza memiliki sensitivitas rendah untuk dapat mendeteksi H5N1, sehingga adanya gejala klinis dan riwayat pajanan lebih membantu mengindentifikasi infeksi virus H5N1. 27 Mayoritas kasus bepergian ke atau tinggal di area terinfeksi (72,97%), keadaan ini sangat berisiko bagi anak untuk terjadinya kontak baik secara langsung maupun tidak langsung dengan sumber infeksi.…”
Section: Pembahasanunclassified
“…Serum/plasma samples were aliquoted and kept frozen at Ϫ20°C until tested. These samples were previously investigated by HI and microNT assays using KAN-1 virus as the test antigen, and the results were reported (8). Archival serum samples were obtained from 20 H1N1pdm-infected patients with a median age of 20 years (range, 18 to 42 years).…”
Section: Methodsmentioning
confidence: 99%
“…To accomplish this aim, reverse-genetics-derived H4N1 viruses with N1 genomic segments from various origins (rgH4N1 viruses) were constructed and used as test antigens for NI antibody measurement in an enzyme-linked lectin assay (ELLA). (8). This study found that 3 of the H5N1 survivors had mounted an NI antibody response against the homologous and all of the heterologous NAs used (Table 1).…”
mentioning
confidence: 96%
See 1 more Smart Citation